2007
DOI: 10.1161/circresaha.107.148676
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Arteriogenesis by Ultrasound-Mediated VEGF 165 Plasmid Gene Delivery to Chronically Ischemic Skeletal Muscle

Abstract: Abstract-Current methods of gene delivery for therapeutic angiogenesis are invasive, requiring either intraarterial or intramuscular administration. A noninvasive method of gene delivery has been developed using ultrasound-mediated destruction of intravenously administered DNA-bearing carrier microbubbles during their microcirculatory transit. Here we show that chronic ischemia could be markedly improved by ultrasound-mediated destruction of microbubbles bearing vascular endothelial growth factor-165 (VEGF 165… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
138
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 34 publications
2
138
0
Order By: Relevance
“…In line with the complexity of the angiogenic process, multiple signaling molecules play stagespecific roles in coordinating new blood vessel growth (43). Ischemic hindlimb muscle was collected 28 days postligation, at a time when the levels of factors such as VEGF-A, Ang2, and SDF-1␣ that are activated early in angiogenesis have returned back to baseline (23). In contrast, Ang1 expression is often maintained for weeks after ischemia onset (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the complexity of the angiogenic process, multiple signaling molecules play stagespecific roles in coordinating new blood vessel growth (43). Ischemic hindlimb muscle was collected 28 days postligation, at a time when the levels of factors such as VEGF-A, Ang2, and SDF-1␣ that are activated early in angiogenesis have returned back to baseline (23). In contrast, Ang1 expression is often maintained for weeks after ischemia onset (23).…”
Section: Discussionmentioning
confidence: 99%
“…Male athymic nude rats (6 to 8 weeks, Charles River, Montreal, Canada) were obtained and maintained at the St. Michael's Hospital Animal Research Vivarium in a temperaturecontrolled (22°C) room with ad libitum access to commercial irradiated standard rat chow and autoclaved water. Rats underwent unilateral left-sided chronic hindlimb ischemia induction as described previously (23). Briefly, rats were anesthetized with inhaled isoflurane (2% to 3%).…”
Section: Unilateral Chronic Hindlimb Ischemia Model Tissue Preparatimentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using microbubbles driven by ultrasound in the megahertz frequency range have shown initial success in delivering therapeutic payloads in in vitro (6-10) and animal models (11)(12)(13). The delivery efficiency, however, remains inferior to that demonstrated via viral methods (4), in large part due to an incomplete physical, mechanistic understanding of the manner in which acoustic cavitation alters endothelial membrane permeability.…”
mentioning
confidence: 99%
“…Most studies involve pDNA, associated with a microbubble [47] or co-administred [48,49] with them. Due to its negative electrostatic loading pDNA will not penetrate into cells, but if it is located near a microbubble imploding in the vicinity of a cell it may profit from the temporal permeablization of the cell membrane (sonoporation) [50].…”
Section: Large Therapeutic Moleculesmentioning
confidence: 99%